Physical properties of Tld, Sog, Tsg and Dpp protein interactions are predicted to help create a sharp boundary in Bmp signals during dorsoventral patterning of the Drosophila embryo. - Shimmi, O.; O'Connor, M.B. (Development, 2003)
Dorsal cell fate in Drosophila embryos is specified by an activity gradient of Decapentaplegic (Dpp), a homologue of bone morphogenetic proteins (Bmps) 2/4. Previous genetic and biochemical studies have revealed that the Sog, Tsg and Tld proteins modify Dpp activity at the post-transcriptional level. The predominant view is that Sog and Tsg form a strong ternary complex with Dpp that prevents it from binding to its cognate receptors in lateral regions of the embryo, while in the dorsal-most cells Tld is proposed to process Sog and thereby liberate Dpp for signaling. In this model, it is not readily apparent how Tld activity is restricted to the dorsal-most cells as it is expressed throughout the entire dorsal domain. In this study, additional genetic and biochemical assays were developed to further probe the relationships between the Sog, Tsg, Tld and Dpp proteins. Using cell based assays, we find that the dynamic range over which Dpp functions for signaling is the same range in which Dpp stimulates the cleavage of Sog by Tld. In addition, our data supports a role for Tsg in sensitizing the patterning mechanism to low levels of Dpp. We propose that the strong Dpp concentration dependence exhibited by the processing reaction, together with movement of Dpp by Sog and Tsg protein can help explain how Tld activity is confined to the dorsal-most region of the embryo through formation of a spatially dependent positive and negative reinforcement loop. Such a mechanism also explains how a sharp rather than smooth signaling boundary is formed.